KEY ASPECTS OF REVIVING INVESTMENT ACTIVITY IN THE CONSTRUCTION SECTOR UNDER MARTIAL LAW - Hbur, Zoriana (Public Management and Policy, 2025)
This article examines the dynamics of capital investment in Ukraine’s construction sector from 2021 to 2024 through the lens of unprecedented challenges caused by full-scale armed aggression. It is established that a key trend during this period was the reorientation of investments from residential construction to engineering infrastructure, reflecting shifts in economic priorities under wartime conditions. The sharp decline in investment volumes in 2022 is attributed to the physical destruction of assets, loss of infrastructure access, and increased investment risks. The article highlights the gradual recovery of investment activity in 2023–2024, indicating the adaptation of institutional mechanisms to the realities of prolonged conflict. Particular emphasis is placed on financing critical infrastructure, especially water supply systems, energy facilities, and transport logistics. The relevance of developing a new model for strategic planning in the construction sector—capable of ensuring sustainable functioning under martial law—is substantiated. It is determined that an effective investment strategy should involve the implementation of financial and economic tools focused on risk mitigation and capital mobilization. Key barriers include high interest rates, limited access to long-term financing, and regulatory instability. The potential of public-private partnerships is revealed as a mechanism for implementing large-scale infrastructure projects. The introduction of specialized funds, war risk insurance mechanisms, and tax incentives for investors is deemed expedient. The article emphasizes that the adaptation of best European practices in investment management can enhance the institutional capacity of the state. The importance of digital technology adoption in planning and monitoring construction project implementation is underscored. Innovations such as Building Information Modeling (BIM) and Geographic Information Systems (GIS) are shown to improve decision-making efficiency. There is a recognized need for the development of human capital in the sector and the modernization of production capacities. International financial support, including agreements with the European Investment Bank, is noted to open new opportunities for attracting concessional resources. Finally, the unification of procedures, transparency of expenditures, and inter-institutional coordination are identified as foundational elements for post-war reconstruction.